Os aposentados economicamente ativos e a constituição de vínculos entre indivíduo e trabalho - Algeri, Vanessa (2015)
The work, through history, was part of an individual's life. The man in his job search their livelihood and that of his family, as well as recognition, status and establishing emotional bonds. In the past, the individual stays working until retired, after withdrawing from the labor market. Currently, linked with increased life expectancy, denotes to stay or return retired in the labor market. The objective of this research between economically active and retired work. The purpose it was intended to the study contribute to the debate and public policy development, targeted to workers who are retired and need to work. These people live in Estação-RS, and the Health Community Agents who are part of the Health Team county family nominated it. The sample consists in 125 participants, men and women, chosen through simple random sampling, which they were submitted to a form. For this analysis, we used hypothesis test, estimates, unilabiate and multivariate association measures, through IBM SPSS STATISTICS 22 application. The results were compiled in two scientific publications. First, it is entitled in Overview work, years of education and income: economic evidence active retired, which aimed to analyze the investigated variables working relationship, years of study and income of the economically active retired and job. As a result it was identificated that the study participant, the retired economically active, to set up, an informal job s relation, in different activities; it showed that the variable years in education is directly linked to formal employment and increasing income. Second, production aims to identify the reasons for retired remain economically active and is being finalized